Quality of Work Life and Organizational Commitment of Employees - Allimar M. Nuevo (Journal of Social Responsibility, Tourism and Hospitality, 2023)
In the highly competitive realm of business, it is crucial for organizations to be profitable in order to progress. However, a significant challenge faced in today’s cutthroat environment is retaining skilled employees and fostering their dedication. The commitment of employees is a critical issue that organizations currently grapple with, as it plays a vital role in attaining overall organizational success. This study aspired to find out which domain in the quality of work life significantly influences the organizational commitment of hotel employees. The quantitative non-experimental design utilizing causal-effect was used in the study. The respondents of the study were the 200 hotel employees with diverse range of working experience and levels of academic background that are in the hospitality and tourism industry. Mean, Pearson-r and Regression Analysis were the statistical tools employed to interpret the data gathered. The findings of the study revealed a very high level of quality of work of hotel employees in terms of work environment, employee welfare and well-being, work-life balance, job characteristics and compensation and benefits. It was also revealed that the organizational commitment of employees was high level in terms of affective commitment, continuance commitment and normative commitment. The result of the study confirmed that there was a significant association between the quality of work life and organizational commitment of employees. It was also found that the domains of quality of work life showed that compensation and benefits, employee welfare and wellbeing and work-life balance significantly influenced the organizational commitment of employees. Lastly, when an individual finds satisfaction in their job and experiences a positive quality of life, they demonstrate a strong sense of commitment and actively contribute to the success of the organization.